2016
DOI: 10.1152/ajprenal.00123.2016
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth restriction programs an accelerated age-related increase in cardiovascular risk in male offspring

Abstract: Placental insufficiency programs an increase in blood pressure associated with a twofold increase in serum testosterone in male growth-restricted offspring at 4 mo of age. Population studies indicate that the inverse relationship between birth weight and blood pressure is amplified with age. Thus, we tested the hypothesis that intrauterine growth restriction programs an age-related increase in blood pressure in male offspring. Growth-restricted offspring retained a significantly higher blood pressure at 12 but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
3
11
0
Order By: Relevance
“…There was a trend for increased total protein levels in sham rats treated with 5 mg/kg per day ELP‐VEGF, but it is possible that degradation products of the infused protein itself are being detected in this assay. It has been widely studied that the RUPP surgery induces fetal resorption and intrauterine growth restriction of the surviving pups 72, 73, 74, 75, 76. Fetal resorption and fetal growth restriction was observed in our study as well (Table 1 and Figure S3), validating the success of the RUPP procedure in our rats.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…There was a trend for increased total protein levels in sham rats treated with 5 mg/kg per day ELP‐VEGF, but it is possible that degradation products of the infused protein itself are being detected in this assay. It has been widely studied that the RUPP surgery induces fetal resorption and intrauterine growth restriction of the surviving pups 72, 73, 74, 75, 76. Fetal resorption and fetal growth restriction was observed in our study as well (Table 1 and Figure S3), validating the success of the RUPP procedure in our rats.…”
Section: Resultssupporting
confidence: 87%
“…It has been widely studied that the RUPP surgery induces fetal resorption and intrauterine growth restriction of the surviving pups. [72][73][74][75][76] Fetal resorption and fetal growth restriction was observed in our study as well (Table 1 and Figure S3), validating the success of the RUPP procedure in our rats. There were no differences in total litter size among the treatment groups, but all RUPP-treated rats had more resorbed fetuses than sham-treated rats did (Table 1 and Figure S3).…”
Section: Other Effects Of Elp-vegf Treatment In Pregnant Ratssupporting
confidence: 88%
“…We previously reported that circulating levels of testosterone are significantly elevated in mIUGR relative to age-matched control in young adulthood [ 22 ] but no longer differ by 12 months of age [ 23 ]. To determine if changes in testosterone correlate with altered glucose homeostasis, we performed an oral glucose tolerance test 6 weeks after sham, castration, or castration with testosterone replacement.…”
Section: Resultsmentioning
confidence: 99%
“…Castration abolishes the increase in blood pressure in mIUGR [ 22 ] indicating the permissive role of testosterone in the etiology of increased cardiovascular risk originating in early life. However, in later life testosterone associated blood pressure does not remain elevated in mIUGR relative to their normal birth weight counterparts [ 23 ]. Whether IUGR programs impaired glucose homeostasis in mIUGR, and whether a decrease in endogenous testosterone plays a role in the development of this impairment are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In each of these models, progeny are lighter at birth but catch up in body weight to that of controls during or before adulthood. 37,[41][42][43][44][45][46][47][48][49][50][51] Development of obesity is variable, with obesity reported in adult female, but not male, RUPP rats with ageing, 52,53 but normal body and central fat abundance in adult progeny of sFlt1-transduced mice of both sexes. 54 Likewise, effects of in utero exposure to a preeclamptic phenotype on postnatal glucose tolerance are sex-and agedependent in the RUPP rat, 53,55 L-NAME-treated rat 56 and sFlt1-transduced mice 51 models of PE.…”
Section: Developmental Programming Of Cvd Risk By In Utero Exposure Tmentioning
confidence: 99%